PENGGUNAAN ANALISIS BREAK EVEN POINT (BEP) DALAM PERENCANAAN LABA TAHUN 2019 PEMBUDIDAYAAN LELE H. WAHIB LERAN MANYAR GRESIK - Astanto SE.,MM, Denny (Fakultas Ekonomi Universitas Gresik, 2020)
The research aims to know break even point (BEP) analysis for profits planning ofH. Wahib catfish cultivation Leran Manyar Gresik. The company use the break even point analysis to figure out the profit volume estimation of cost, level of sales and production volume in achieving profit planning.Based on data analysis break even from catfish selling in 2016 was reached in the amount of 1.671 Kg or Rp. 25.079.365,- while in 2017 break even from catfish selling was reached in the amount of 1.512 Kg or Rp. 23.636.363,- and in 2018Ãƒâ€šÃ‚Â break even from catfish selling was reached in the amount of 1.638 or Rp. 26.470.588,-.Results of this study was the differences in the achievements of break even points in Rupiahs and in quantity in each year. This is because of differences in the magnitude of the costs incurred by the company every year. However for each year, that a sample taken by the author can be seen that the sales made by the company is good and always be above the break even point, which means the company has been able to achieve a profit every year.